Retraction Note: MicroRNA-30d promotes angiogenesis and tumor growth via MYPT1/c-JUN/VEGFA pathway and predicts aggressive outcome in prostate cancer - Zhuo-yuan Lin; Guo Chen; Yan-qiong Zhang; Hui-chan He; Yu-xiang Liang; Jian-heng Ye; Ying-ke Liang; Ru-jun Mo; Jian-ming Lu; Yang-jia Zhuo; Yu Zheng; Fu-neng Jiang; et al. (Molecular Cancer, 2023)
This article has been retracted. Please see the Retraction Notice for more detail: https://doi.org/10.1186/s12943-017-0615-x.